Post-Orthodontic Evaluation of Incisor Position on Class I Malocclusion Patients: A Radiographic Study - Valerie Kartini; Miesje Karmiati Purwanegara; Muhammad Sulaiman Kusumah Adiwirya (Journal of Indonesian Dental Association, 2025)
Background: Malocclusion is the irregularity of teeth, considered as an oral health problem resulting from various etiological factors, causing esthetic dissatisfaction to functional impairment. Malocclusions must be fixed by orthodontic treatment. Achieving proper incisor inclination and angulation is essential for orthodontic treatment stability and facial harmony. However, limited evidence exists regarding post-treatment incisor positioning in Class I skeletal malocclusion patients within the Indonesian population. Objective: This study aimed to analyze the post-treatment inclination and angulation of maxillary and mandibular incisors in Class I skeletal malocclusion patients and to evaluate whether these parameters fall within established cephalometric norms. Methods: A descriptive cross-sectional analysis was conducted using secondary cephalometric data from 96 post-treatment medical records. Incisor inclination was measured using U1–SN, U1–PP, L1–MP, and IMPA angles, while angulation was assessed for upper and lower central incisors. Results: The mean upper incisor angles were 106° (U1-SN) and 115° (U1-PP), and the lower incisor angles were 94° (L1-MP) and 96° (IMPA). The mean angulation of individual incisors was approximately 89–91° for both upper and lower central incisors. Conclusion: Pre-adjusted bracket systems used in the study effectively guide incisors toward favorable positioning within normal ranges, with minor variations such as the IMPA angle, supporting both functional and esthetic outcomes.This study took the initiative to describe both post-treatment upper and lower incisor position in Indonesian orthodontic patients.